Identification of the Zn substitution sites in La-Zn substituted SrAl12O19 from Al-27 solid-state NMR studies - Baby, Bindhu; Dey, Krishna K.; Ajithkumar, Thalasseril G.; Joy, Pattayil A. (Journal of the American Ceramic Society, 2014)
The La-Zn substituted hexagonal strontium aluminate, Sr1-xLaxAl12-xZnxO19, with the magnetoplumbite structure and having five different coordination environments for Al with different symmetries, is investigated using Al-27 solid-state NMR to get detailed information on the sites of substitution of Zn and the associated changes in the local coordination environments of Al. The objective of the study was to get information on the local structural variations in the isostructural La-Co substituted strontium ferrite, Sr1-xLaxFe12-xCoxO19, showing enhanced magnetic performance on substitution. The NMR studies on the aluminate give direct evidence for the sites of substitution and the changes in the local coordination environments. It is found that Zn is substituted at the 2a and 4f(2) AlO6 octahedral sites. However, an interesting observation from the NMR studies is the stabilization of the Al site occupancy at the penta-coordinated 2b site over the distorted tetrahedral 4eAl site, without any substitution at these sites. Large changes in the quadrupolar coupling constant of the 2a and 4e sites are observed between x=0.2 and 0.3, corresponding to the compositional region showing higher performance in the case of Sr1-xLaxFe12-xCoxO19, indicating the role of distortion of local coordination environments on suitable substitution in controlling the performance parameters.

Metamagnetism in nanosheets of Co-II-MOF with T-N at 26 K and a giant hysteretic effect at 5 K - Gupta, Kriti; Dadwal, Arun; Rana, Shammi; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2018)
Herein, we have synthesized at room-temperature two-dimensional nanosheets of a MOF comprised of cobalt(II) ion with benzenedicarboxylic acid ligand, which exhibited unusual magnetic properties. Direct-current magnetic susceptibility revealed an anti-ferromagnetic (AFM) transition at 26 K (Neel temperature, T-N) followed by a canting of the spin moments along with the concomitant appearance of a sigmoidal-shaped magnetization versus field (M-H) curve at 15 K. Such a canted AFM ordering led to nonzero remnant magnetization with a remarkably high coercive field of similar to 10 kOe at 5 K. Metamagnetism was further: substantiated by the alternating-current magnetic susceptibility measurements.

Embedding S=1/2 Kagome-like lattice in reduced graphene oxide - Gupta, Kriti; Jha, Plawan Kumar; Dadwal, Arun; Debnath, Anil K.; Jaiswal, Ishan; Rana, Shammi; Joy, Pattayil A.; Ballav, Nirmalya (Journal of Physical Chemistry Letters, 2019)
An elegant platform to explore frustrated magnetism is the kagome spin lattice. In this work, clinoatacamite, a naturally occurring S = 1/2 kagome-like antiferromagnetic insulator, is synthesized in water at ambient pressure for the first time from a cuprous chloride (CuCl) precursor whereby Cu(I) was spontaneously oxidized to Cu(II) in the form of clinoatacamite [Cu-2(OH)(3)Cl] with a simultaneous reduction of graphene oxide (GO) to reduced graphene oxide (rGO) in one pot. A stable nanocomposite of phase-pure clinoatacamite nanocrystals embedded in the rGO matrix was isolated. The clinoatacamite-rGO nanocomposite was determined to be magnetically active with a markedly enhanced coercive field of similar to 2500 Oe at S K as well as electronically active with a conductivity value of similar to 200 S.m(-1) at 300 K. Our results illustrate an avenue of combining exotic magnetic and electronic lattices without impeding their individual characteristics and synergistically generating a new class of magnetic semiconductors.

Exploring magnetic XY behavior in a quasi-2D anisotropic triangular lattice of Cu(II) by functionalized graphene - Gupta, Kriti; Dadwal, Arun; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2020)
Study on magnetism in two-dimensional (2D) spin-lattices is advancing rapidly. In this work, phase-pure botallackite (Bo) (Cu-2(OH)(3)Br), a quasi-2D S = 1/2 anisotropic triangular spin-lattice is stabilized over 2D reduced graphene oxide (rGO) nanosheets via simple oxidation-reduction reaction chemistry. In comparison to polycrystalline Bo, such an anchoring resulted in the oriented growth of Bo crystallites in the Bo-rGO system. The Bo-rGO nanocomposite was found to be magnetically active with a Neel transition at 8.9 K, crossing over to possible XY anisotropy at similar to 5 K-as revealed by complementary dc and ac susceptibility measurements-an unprecedented observation in the field assigned to an interfacial effect. This work demonstrates the potential usage of nonmagnetic 2D functionalized graphene to significantly modulate the magnetic properties of 2D spin-lattices.

Integrating structurally perfect s=1/2 kagome-lattice with reduced graphene oxide - Gupta, Kriti; Dadwal, Arun; Ninawe, Pranay; Joy, Pattayil A.; Ballav, Nirmalya (Journal of Physical Chemistry C, 2020)
S = 1/2 kagome-lattice hydroxychlorides are promising candidates for realizing the elusive quantum spin liquid (QSL) state. Herbertsmithite [Cu3Zn(OH)(6)Cl-2], a naturally occurring hydroxychloride mineral from the class of atacamites {[Cu-4-xMx(OH)(6)X-2] where M = Zn, Cu, Co, Ni and X = Cl, Br, I}, is one of the most appealing systems to study the QSL state because of the presence of a structurally perfect S = 1/2 kagome-lattice. It is an electrical insulator. However, realizing phase-pure herbertsmithite without imposing harsh reaction conditions remained synthetically challenging. In this work, for the first time, we have synthesized phase-pure herbertsmithite as well as its structural analogue paratacamite, [ZnxCu4-x(OH)(6)Cl-2; 0.33 = x < 1], at ambient reaction conditions. Furthermore, taking graphene oxide (GO) as an additional precursor in the reaction mixture, we have successfully integrated phase-pure crystallites of herbertsmithite (H) and paratacamite (P) with nanosheets of semiconducting and diamagnetic reduced graphene oxide (rGO) by in situ oxidation-reduction reaction. The isolated H-rGO and P-rGO systems were found to be magnetic semiconductors inheriting strong spin frustration from H and P, and semiconductivity from rGO. The H-rGO system in particular exhibited negative Seebeck coefficient (n-type semiconductor) with a thermoelectric power factor of 0.1 mu W center dot m(-1)center dot K-2 at 400 K. We anticipate the simple chemical principles outlined in this work to be useful for studying a variety of complex QSLs including electron doping. Also, semiconducting and rather unconventional materials of such metal oxochlorides with rGO isolated here need further exploration in view of thermoelectric applications.

Magnetic and magnetoelastic properties of Ni-substituted cobalt ferrite - Bhame, Shekhar D.; Shirolkar, Mandar M.; Joy, Pattayil A. (IEEE Magnetics Letters, 2021)
In this letter, magnetic and magnetostriction studies were performed on spinel ferrite Co1-xNixFe2O4 (CNF series) with 0.0 < x < 0.5. All the samples were synthesized by the conventional ceramic method and confirmed to be forming pure spinel phase. The unit cell parameter showed gradual decrease with increasing Ni content. A linear decrease in saturation magnetization (M-s) and coercivity (H-c) was observed with increasing Ni substitution, which could be attributed to reduced magneto-crystalline anisotropy. The room temperature magnetostriction studies revealed a slow decrease in maximum magnetostriction, and interestingly, for 20% reduction of cobalt concentration, i.e., for x = 0.2, a magnetostrictive strain of -164 ppm and substantially high stress sensitivity of -56 x 10(-6) A(-1) m were observed, making Co0.8Ni0.2Fe2O4 suitable for application as a magnetostrictive stress-sensing material.
Keywords: Ferrite; Magnetism in solids; Magnetostriction; oxide; stress sensing

Possible electron doping of geometrically perfect spin-1/2 kagome-lattice barlowite by reduced graphene oxide - Gupta, Kriti; Ninawe, Pranay; Jain, Anil; Dadwal, Arun; Anas, M.; Malik, V. K.; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Physical Review B, 2021)
Doping of quantum spin liquid (QSL) insulators by electron or hole leads to intriguing phase transitions to metallic and superconducting states. The barlowite family with geometrically perfect S = 1/2 kagome planes and tunable interkagome coupling is an emerging platform to realize spin-ordered, valence bond crystal, QSL states. Theoretical investigations on electron doping revealed localized states in the band gap of barlowite unlike metallicity in cuprate (Nd2CuO4). We present successful anchoring of phase-pure barlowite crystallites onto reduced graphene oxide (rGO). The resulting barlowite-rGO system was found to be an electrical semiconductor with Arrhenius activation energy of 0.07 eV. Semiconducting properties of the barlowite-rGO system were further modulated with retention of structural integrity. We have attributed such a transformation of electrical transport response to plausible electron doping thereby making charge-doping experiments on barlowite and its analogs propitious.

Magnetostriction studies on transition metal substituted cobalt ferrite - Bhame, D. Shekhar; Bhapkar, Abhishek; Shirolkar, Mandar M.; Joy, Pattayil A. (Journal of the Indian Chemical Society, 2022)
Structural, magnetic and microstructural properties of transition metal (TM) substituted cobalt ferrite Co0.9TM0.1Fe2O4 (where TM = Ti, Cr, Mn, Ni and Cu and Zn) were investigated. The present study shows marked dependence of the magnetostriction on the concentration of the substituted transition metal ions for Cobalt in CoFe2O4. The magnetic characteristics of the prepared compositions such as coercivity, anisotropy constant and saturation magnetization changed significantly on transition metal substitution. The present study shows the way to tune the anisotropy of cobalt ferrite by effective substitution of other transition metal ions for Co which subsequently affects the stress sensing performance by changing the slope of the magnetostriction curve. Apart from the magnetic properties the microstructure can also be effectively modified by substitution of other transition metal ions. Only 10% substitution of cobalt showed drastic influence on magnetostriction and slope of magnetostriction curve. The composition with 10% nickel Co0.9Ni0.1Fe2O4 exhibited maximum slope for the magnetostriction curve of -53.7 ppm/Oe, along with reasonably high magnitude of strain of 186 ppm making it a suitable for exploring stress sensing applications.
Keywords: Ferrite; Magnetoelastic; Magnetostriction; oxide; stress sensing